The language of media supporting peace journalism - Wibowo, Agus Hari (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper attempts to explore the role of the language of media, particularly newspapers, in making peace of a heterogeneous society in Indonesia. As one of mass media, newspapers can play a significant role to create peace of the society. In reporting news, the newspaper reporters might use some means of language aspects to avoid the use of expressions which potentially provoke conflict. Striving to prevent conflict among parties means that the media have supported peace journalism. This paper examines the employment of linguistic devices used by the journalists of Indonesian newspapers in endeavours to lessen the potency of conflict and to build harmony of the society. The efforts to create peace in Indonesia should constantly maintain, since Indonesia is a country with multi ethnics, religions, languages, and social backgrounds. Maintaining the peaceful condition of the country is the task of Indonesian journalists. The data were taken from two regional Indonesian newspapers published in Semarang and Surakarta, Jawa Tengah, i.e., Suara Merdeka and Solopos. The result shows that the newspapers, to some extent, exploit the linguistic devices to create harmony through unnamed body/society, general expression, implicit expression, and hedging devices. As the focus of the study is on language point of view, it will be more fruitful if this study is completed with the study from communication and journalism point of view.